An analysis of the nutritional and behavioral status of drug addicts (Research, Society and Development, 2023)
Drugs are a public health problem that is increasingly growing and impacting the whole world, with Brazil being one of the largest consumers. In addition, it is a disease that impacts the human being, in all areas and that needs monitoring by a multidisciplinary team, which can cause eating disorders and, subsequently, lead to obesity, however, this topic still needs studies. In view of the fact that this is a topic of great importance for public health, the objective of this study was to analyze the nutritional and behavioral status of drug addicts. A cross-sectional, descriptive, exploratory and qualitative study was conducted. The questionnaires applied were FFQ, EAT 26, ASSIST test and 24-hour recall, in addition to anthropometric measurement, in a sample of individuals who are undergoing treatment for drug use, at the Crescer Institute, in two administrative regions of the Federal District. Through the results obtained it was observed that 84% of the sample were users of multiple drugs and in relation to eating behavior after the beginning of treatment, 63.2% of the participants reported increased intake of sweet foods. Regarding nutritional status, most fall under the classification of underweight and 24.3% were at risk of developing an eating disorder. Based on the above, a multiprofessional therapy is essential, highlighting the role played by the nutritionist, since it is necessary to make adjustments in the nutritional therapy of the individual, aiming to reduce possible damages generated in the eating habit, promoting health and quality of life.